2011
DOI: 10.1143/apex.5.017001
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Potassium Ion Release Due to Apoptosis with Cell-Based Transparent-Gate Transistor

Abstract: We monitored programmed cell death (apoptosis) in a real-time, direct and noninvasive manner using a cell-based transparent-gate transistor (TGT). Indium–tin-oxide (ITO) was utilized as a gate material, because cultured cells could be easily observed by microscopy due to its transparency. After induction of apoptosis on the cell-based TGT, the change of threshold voltage decreased gradually, which resulted from potassium ion release caused by apoptosis. The morphological change of apoptotic cells was simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In addition, ISFET sensors can be fabricated in large numbers using standard lithographic processes. Recent studies have demonstrated the use of ISFETs for measuring ion flux from single cells plated and grown on coated (Straub et al, 2001; Wrobel et al, 2005; Chang et al, 2012) or uncoated (Yu et al, 2007; Gebinoga et al, 2010; Sakata et al, 2012) sensors. However, the application of ISFETs in multi-well plate, parallel measurement configurations for ion efflux analysis has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ISFET sensors can be fabricated in large numbers using standard lithographic processes. Recent studies have demonstrated the use of ISFETs for measuring ion flux from single cells plated and grown on coated (Straub et al, 2001; Wrobel et al, 2005; Chang et al, 2012) or uncoated (Yu et al, 2007; Gebinoga et al, 2010; Sakata et al, 2012) sensors. However, the application of ISFETs in multi-well plate, parallel measurement configurations for ion efflux analysis has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…; Sakata & Miyahara ; Sakata et al . , ), based on the detection of changes in ionic charge density induced by cellular activities. In our previous works, field‐effect transistor (FET) biosensors monitored some cellular functions in real time, such as cellular respiration and programmed cell death (apoptosis), on the basis of ionic charges (Sakata & Miyahara ; Sakata et al .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, field‐effect transistor (FET) biosensors monitored some cellular functions in real time, such as cellular respiration and programmed cell death (apoptosis), on the basis of ionic charges (Sakata & Miyahara ; Sakata et al . , ). Such ionic charges have to be selectively detected around a cell/sensor interface depending on the cellular functions of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field effect transistor (FET)-based biosensing systems have been proposed for some applications such as label-free DNA sequencing, [15][16][17] immunological assay [18] and cellular functional analysis. [19][20][21] In particular, FET-based biosensors are suitable for the detection of small molecules such as glucose as long as they have molecular charges. In the case of saccharide sensing, the coating of phenylboronic acid (PBA) derivatives on the gate surface is effective for the detection of low-molecular-weight saccharides such as glucose based on the principle of FETs, because the binding of PBA molecules with saccharide increases the density of negative charges in their conjugate on the basis of the equilibrium reaction.…”
Section: Introductionmentioning
confidence: 99%